The Impact of Unequal Marriage on Household Harmony (Case Study in Sungai Penuh City, Jambi) - Rasidin, Mhd.; Natardi, Natardi; Witro, Doli (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
In the current era of modernization, equal is often interpreted with meaning in terms of social standing, equal in descendants, and balanced in ownership of property. Based on observations made by the author in Sungai Penuh City, Jambi, several community opinions were found that said equal was equal in social status, descent, and wealth. This is often discussed when someone is about to get married, which is a consideration given by his family, especially his parents are to see prospective son-in-law based on social status, whose offspring, and how many prospective daughters-in-law have property. This study aims to examine in depth the case of an unequal marriage and its impact on household harmony that occurred in Sungai Penuh City, Jambi. The writing of this article uses a qualitative research method using field data in Sungai Penuh City. Data collection methods used are observation, interviews, and documentation. The technique that the author used in this research is to use qualitative analysis consisting of domain analysis, taxonomic analysis, and componential analysis. The results of the study show that there are two views of the Sungai Penuh City community on equal issues in marriage, namely people who are concerned with social status (descent and wealth) and idealistic community views with Islamic teachings.